Thromboxane-induced contractile response of mesenteric arterioles is diminished in the older rats and the older hypertensive rats - Zhang, Min; Li, Chunshu; He, Chunxia; Cui, Yiqin; Li, Yuan; Ma, Ying; Cheng, Jun; Wen, Jing; Li, Pengyun; Yang, Yan (Frontiers in Pharmacology, 2022)
Nearly all physiological processes are controlled at some level by G-protein coupled receptors (GPCRs) signaling activity. The thromboxane A2 (TXA2) receptor (TP) is a member of the GPCRs family. The ultimate effect of TP receptor activation depends on the availability of specific G proteins, which in turn depend on the cell type and tissue, as well as the disease state. However, the roles of TXA2-TP signaling pathway executed under disease states are poorly defined. In this study, 16-week-spontaneously hypertensive rats (SHR), the 18-month-SHR (OldSHR), and the age-matched Wistar-Kyoto (WKY) rats were used to study the vasoconstriction of mesenteric resistance artery induced by TP-specific agonist U-46619. We found that vasoconstriction induced by U-46619 was significantly attenuated in OldWKY and OldSHR, and that these mesenteric arteries with impaired response to U-46619 responded strongly to the adrenergic receptor agonist phenylephrine. Similar vascular responses to U-46619 were obtained in endothelium-denuded mesenteric arteries. Accordingly, the expression of TP membrane protein in mesenteric vessels was decreased, and the endogenous TP competitor 8, 9-EET in serum was increased, which were partly responsible for the decreased vascular reactivity of U-46619. Decreased TP membrane expression was associated with TP endocytosis, which involved actin cytoskeletal remodeling, including increased ratio of F-actin/G-actin in OldWKY and OldSHR. Hence, we revealed the effects of TXA2 and its receptors on blood vessels and found that TXA2-TP prostaglandin signaling pathway was impaired in older adults, which would facilitate the creation of “precision therapeutics” that possess selective efficacy in diseases.